Akteursbasierte Simulation der energetischen Modernisierung des Wohngebäudebestands in Deutschland - Stengel, Julian (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2014)
In this book, the stakeholder-based residential building and household simulation model AWOHM is developed and applied to the Federal Republic of Germany. It aims at the identification and the conceptual design of adequate policy instruments in the field of residential/domestic heat use, with a focus on energy-related refurbishments. The model application results in policy instruments that are adapted to the characteristics of the buildings as well as their owners and users.